Systematic Literature Review: Problems Of Learning Business And Management Through Dual System Education Program (PSG) - Dodyk Brahmatiyo; Narisin Narisin; Sri Wileng; Aniek Indrawati; Ludi Wishnu Wardana; Wardana Wardana; A’isy Fiklil; Nafisah Nafisah (International Journal of Business and Quality Research, 2023)
In its planning, this Industrial Work Practice involves several parties, namely the school, students, parents, and partner institutions (Business World/Industry World). 2) Organizing Industrial Work Practices Organizing Industrial Work Practices is one of the efforts to optimize existing resources at school and in partner institutions (Business World/Industry World). 3) Implementation of Industrial Work Practices. Preparing students to enter the workforce and developing professional attitudes, preparing students to be able to choose a career, be competent and self-development, preparing a middle-level workforce to fill the needs of the business world and the industrial world, preparing graduates to become productive, active and creative citizens . The research method uses a systematic literature review. Research data was obtained through internet searches regarding dual system education program journals published 2017-2023. The number of journals analyzed were 8 journals. The data is used to identify and analyze the factors that influence how dual system education programs are analyzed qualitatively. In terms of the attitude of implementers, a good understanding of the program has an impact on the attitudes taken by policy implementers. The school and partner institutions have shown a high commitment to the successful implementation of PSG. The cooperation agreement made between the school and the partner institution has been able to make the process of implementing Industrial Work Practices which is a manifestation of implementing PSG run as expected. Meanwhile, the response from the targets and policy implementers was also very good. Almost all the teachers who were involved, both in the framework of practical activities at school and as mentors, had carried out their activities seriously. It's just that for students there are indeed some students who are not serious about implementing industrial work practices in the business/industry world